(untitled) (Hekima Review, 2016)
The book HIV&AIDS in Africa: Christian Reflection, Public Health, Social Transformation gives a comprehensive look at the HIV/AIDS scourge in Africa. Drawn from diferent felds of study, scholars and experts over their various perspectives on the pandemic: sociological, theological, ecclesiological, public health to mention the most obvious. The book composed of seven parts. Part one explicates sociohistorical, cultural, and political context of the AIDS pandemic. Festo Mkenda begins this part by tracing the socio-historical facts about HIV/AIDS to help us theologize anew and to see the reality of HIV/AIDS accurately for purposes of discerning opportunities to determine appropriate action. Mkenda argues that inadequate political responses about the origin of the pandemic accounts for the devastation of AIDS pandemic in Africa. Mkenda attributes weak healthcare system in Africa to inadequate “socio-economic hardware”. He presents various opportunities to mitigate the pandemic: appreciation of social connectedness, open conversation on sexuality and strengthening active role of women and the African family.